The Influence of Work Discipline, Work Environment and Work Motivation on Employee Performance with Reward as an Intervening Variable - Bagus Prakoso; Susanti Widhiastuti (www.amertainstitute.com, 2026)
This research aims to test and analyze the influence of work discipline, work environment, and work motivation on employee performance with rewards as an intervening variable at PT. XYZ. This research was motivated by fluctuations in the achievement of monthly operational targets which were not yet optimal in the Kotabumi Unit as well as gaps in the results of previous research (research gaps) related to the determining factors of employee performance. The research method used is a quantitative approach with a causality design. The population in this study was 106 employees. Sampling used a saturated sampling method (census), so that all members of the population were used as research respondents. The data analysis technique uses the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) with the help of SmartPLS software version 4.1.1.8. The research results show that directly, work discipline and rewards have a positive and significant effect on employee performance. Work discipline and work motivation have also been proven to have a positive and significant effect on rewards. In contrast, the work environment and work motivation were found not to have a significant direct influence on employee performance. The work environment also has no significant effect on rewards. In testing the mediation effect, rewards were unable to mediate the influence of work discipline or work environment on employee performance. The main findings of this research prove that rewards are able to perfectly mediate the influence of work motivation on employee performance (perfect / full mediation). This main empirical contribution indicates that the abstract potential of internal enthusiasm (motivation) of employees cannot necessarily improve work performance independently, but must be bridged by real reward instruments in the form of incentives based on work volume so that it can be accelerated into concrete work productivity in the field.